Respuesta :
For this case we have the following equation:
[tex] (x - 5) ^ 2 + 3 (x - 5) + 9 = 0
[/tex]
We make the following change of variables:
[tex] u = x-5
[/tex]
We have then:
[tex] u ^ 2 + 3u + 9 = 0
[/tex]
Then, using the quadratic formula we have:
[tex] u = \frac{-3 +/- \sqrt{3^2 - 4(1)(9)}}{2(1)}
[/tex]
[tex] u = \frac{-3 +/- \sqrt{9 - 36}}{2} [/tex]
[tex] u = \frac{-3 +/- \sqrt{-27}}{2} [/tex]
[tex] u = \frac{-3 +/- i 3\sqrt{3}}{2} [/tex]
Solution 1:
[tex] u = \frac{-3 + i3\sqrt{3}}{2} [/tex]
Solution 2:
[tex] u = \frac{-3 - i3\sqrt{3}}{2} [/tex]
Finally, returning the change we have:
Solution 1:
[tex]x1=u1+5=\frac{-3+i3\sqrt{3}}{2}+5[/tex]
[tex] x1 = \frac{1}{2}(7+i3\sqrt{3}) [/tex]
Solution 2:
[tex]x2=u2+5=\frac{-3-i3\sqrt{3}}{2}+5[/tex]
[tex]x2 = \frac{1}{2}(7-i3\sqrt{3})[/tex]
The value of x are as follows;
1 /2 (7 +3i√3 / 2 )
1 / 2 (7 - 3i√3 / 2 )
Using substitution method,
Substitution
Substitution simply means to put in place of another. Therefore, let's replace u in the equation.
u = (x - 5)
(x – 5)² + 3(x – 5) + 9 = 0
u² + 3u + 9 = 0
Quadratic formula
-b ±√b² - 4ac / 2a
where
a = 1
b = 3
c = 9
Therefore,
-3 ± √3² - 4(1)(9) / 2(1)
-3 ± √9 - 36 / 2
-3 ± √-27 / 2
Therefore,
u = -3 + 3i√3 / 2
or
u = -3 - 3i√3 / 2
Finally,
x = u + 5
x = -3 + 3i√3 / 2 + 5 = 1 /2 (7 +3i√3 / 2 )
or
x = -3 - 3i√3 / 2 + 5 = 1 / 2 (7 - 3i√3 / 2 )
learn more on substitution and quadratic formula here: https://brainly.com/question/11540485